PHYSICAL-MECHANICAL PROPERTIES AND PERMEABILITY EVALUATION OF CHITOSAN FILM - Endang Warsiki, Juanda Sianturi dan Titi Candra Sunarti (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTThe aim of this study was to compare the physical-mechanical properties between the packaging film made from chitosan with the garlic extract and the conventional packaging of polypropilene (PP). Garlic extract addition  in this film  resulted  higher thickness and elongation at break compared to the film without garlic extract. However, the film has less strength than others. The results also showed that the properties of break of films based on chitosan were better than those of the commercial film. However, in some other properties, i.e. strength and water vapour  transmission rate, PP was still superior than chitosan film. The chitosan film could  be easily sealed as good  as PP. That means that some part of the films properties is comparable to PP. So far, chitosan film resulted from this study had good prospect as a material to substitute conventional packaging material, such as PP. In addition, the effect of the drawback in permeability could be reduced by adding inert gases or sealing the product in vacuum condition or putting it as secondary or tertiary packaging.Keywords:  packaging film, chitosan, garlic extract, polypropylene